Pemeriksaan Bone Mineral Density dan Pelatihan Senam Osteoporosis Sebagai Upaya Peningkatan Kewaspadaan Osteoporosis pada Penderita Talasemia Mayor - Nyoman Suci Widyastiti; Edward Kurnia Setiawan Limijadi; Meita Hendrianingtyas; Ariosta Ariosta; Dwi Retnoningrum; Dwi Ngestiningsih; Yetty Movieta Nency (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Thalassemia major patients with routine transfusions are at risk of experiencing iron overload and bone turn over disorders which will increase the risk of osteoporosis. Community training activities with BMD examinations and osteoporosis exercise training in thalassemia major patients are expected to identify the prevalence of bone fragility in thalassemia major patients, increase the awareness of thalassemia major patients and their families to the risk of osteoporosis in thalassemia major patients and osteoporosis exercise training as an effort to prevent osteroporosis. The results of BMD on the spine showed 57.1% osteoporosis, 28.6% normal and 14.3% osteopenia. The results of BMD examination on the cervical spine showed 71.4% osteopenia, 21.4% normal and 7.2% osteoporosis. The results of BMD examination on the femur found 50% normal, 42.8% osteopenia and 7.2% osteoporosis. The bone location with the highest percentage of osteoporosis was the spine (57%), and the bone location with the highest percentage of osteopenia was the neck bone (71.4%). The high percentage of osteopenia locations in the cervical spine of thalassemia major patients with repeated transfusions should be become a concern. Based on these findings, we held education and counselling on the risk of osteoporosis in thalassemia patients with repeated transfusions, osteoporosis exercise training and distribution of osteoporosis exercise compact disk (CD) for at home osteoporosis exercise training.